Results of medical treatment with psyllium, lactobacillus, and tryptophan (Plurilac® Trio) in obstructive defecation syndrome - Valiyeva, Sayali; Tiso, Domenico; Cerri, Paolo; Pisciaroli, Antonio; Pietroletti, Renato (Frontiers in Surgery, 2024)
The term obstructive defecation syndrome (ODS) describes a complex condition characterized by defecatory disorders. Such condition represents a significative proportion, estimated up to 30% of patients affected by chronic constipation. At the moment, a large agreement has been reached on diagnostic studies whereas the choice of treatment aimed to improve quality of life and/or to correct the prevalent or all anatomical abnormalities is still controversial.This was a retrospective cohort study on 174 patients out of 232 with ODS observed in a specialized university unit of surgical coloproctology between 2018-2022. Clinical assessment includeded Agachan-Wexner's constipation score and PAC-QoL scores, full digital anorectal examination, anoscopy, RX defecography, uro-gynaecological consultation; functional anorectal testing, endo anal ultrasound and colonscopy were performed in selected cases. Patients were re-evaluated after 8-10 weeks course of medical treatment, based on, high fiber diet and fluid intake, 6 g of psyllium combined with lactobacillus and tryptophan b.i.d.. Results were analyzed by means of Wilcoxon rank-sum test, comparing pre-treatment scores with the results at first follow-up visit.After 8-10 weeks of conservative treatment, 128 patients declared full satisfaction, 29 reported a moderate satisfaction, 17 (9.7%) declared no improvement. Among these latter, there were 5 cases of paradoxical pubo-rectal contraction. The value of Agachan-Wexner's constipation score after treatment was reduced from pre-treatment Agachan-Wexner's constipation score mean value of 23.4 +/-3.7 (mean +/-sd range 15-27) to a mean value of 5.3 +/-0.7 (range 3-8. P<0.001). Quality of life improved as shown by PAC-QoL score indicating sharp amelioration of social relationship.Considering the benefits of conservative therapies, they represent a cornerstone in treatment of this complex disorder. Diet and bulking agents are mandatory treatments prior to any surgical attempt also considering that psychosomatic component of ODS is essential to match patient expectation.